2018
DOI: 10.1177/2165079918774367
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health and Safety Training in Reducing Occupational Injuries Among Harvesting Forestry Contractors in KwaZulu-Natal

Abstract: Forestry work is generally characterized by a combination of personal and environmental risks in health and safety. Employers need to ensure intensive and continuous safety training to mitigate these risks; however, the efficacy of this training is seldom evaluated. The aim of this study was to assess the effectiveness of health and safety training in reducing injuries and improving knowledge, attitudes, and perceptions toward safety among forestry workers in KwaZulu-Natal (KZN), South Africa. A descriptive cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Kisaka-Lwayo and Obi (2012) opined that perception of risk differs between gender groups. Aluko et al (2016) and Nkomo et al (2018) also reported that gender was associated with higher attitudes to occupational hazards and safety practices, though Aluko et al (2016) found no association between gender and perception. This position agrees with Chaswa et al (2020) where they reported that gender had no effect on risk perception among construction workers.…”
Section: Relationship Between Perception Constructs and Personal Charmentioning
confidence: 99%
“…Kisaka-Lwayo and Obi (2012) opined that perception of risk differs between gender groups. Aluko et al (2016) and Nkomo et al (2018) also reported that gender was associated with higher attitudes to occupational hazards and safety practices, though Aluko et al (2016) found no association between gender and perception. This position agrees with Chaswa et al (2020) where they reported that gender had no effect on risk perception among construction workers.…”
Section: Relationship Between Perception Constructs and Personal Charmentioning
confidence: 99%
“…An accident can create a big issue (lousy reputation) for tourist destinations if an accident occurs during observation. Forestry work has significant risks and these losses can cause fatalities, so the use of PPE is necessary (Nkomo et al 2018). Despite using PPE, technical prevention is the most important.…”
Section: Safety Security and Convenience Factors (Elephas Maximus Sum...mentioning
confidence: 99%
“…As principais medidas de segurança a considerar na prevenção de acidentes em operações de colheita florestal São diversas as medidas de segurança e de prevenção de acidentes que podem ser implementadas no sentido de controlar a exposição dos trabalhadores ao risco de acidentes ocupacionais durante as atividades de colheita florestal. Estas focam, essencialmente, a proteção do trabalhador com os EPIs adequados, a formação técnica do trabalhador e a alteração/ajuste da metodologia de gestão desta atividade (Albizu- Urionabarrenetxea et al, 2013;Bligard and Haggstrom, 2019;Borz et al, 2014;Bush et al, 2014;Conway et al, 2017;Gluschkov et al, 2014;Kaakkurivaara and Stampher, 2018;Lagerstrom et al, 2017;Leclercq et al, 2020;Longo et al, 2013;Mylek and Schirmer, 2015;Newman et al, 2018;Nkomo et al, 2018;Schwarz et al, 2016;Unver and Ergenc, 2020;Yovi and Yamada, 2015).…”
Section: Fatores Relacionados Com As Adversidades Ambientaisunclassified